Cultural knowledge, category label, and social connections: Components of cultural identity in the global, multicultural context. Issue 4 (4th September 2013) - Wan, Ching; Chew, Pony Yuen‐Ga
Abstract : Cultural identity refers to the psychological connection between an individual's self and a culture. In this paper, we identify three components that make up an individual's cultural identity – cultural knowledge, category label, and social connections. The cultural knowledge component connects an individual with a culture through the individual's direct endorsement of what are widely known to be the culture's central characteristics. The category label component connects an individual with a culture through the individual's depersonalized membership in a cultural collective. The social connections component connects an individual with a culture through networks of specific social relationships. The three components are conceptually distinct, and yet may have interconnections in influencing the development of cultural identity. We examine the implications of the three components on cultural identification processes in the context of multiculturalism and global cultural contact.